An Analysis of Students’ Mathematical Problem-Solving Ability in Relation to Their Mathematical Anxiety: A Study of Grade VII Students at SMP Muhammadiyah Sokaraja - Oktifiani, Shela; Rahmawati, Lily (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aimed to analyze the mathematical problem-solving abilities of seventh-grade students at SMP Muhammadiyah Sokaraja in relation to the mathematical anxiety they experienced. This research was conducted as qualitative field research, with data collected at SMP Muhammadiyah Sokaraja. The subjects of the study were students from Class VII B. Data were obtained through observation, interviews, and problem-solving tests. The tests were administered to assess students' mathematical problem-solving abilities, which were then categorized into three levels: low, moderate, and high. Students were subsequently observed and interviewed regarding their experiences of mathematical anxiety. These observations and interviews were conducted over three meetings. The findings revealed that students with low problem-solving abilities tended to experience mathematical anxiety in the form of difficulty speaking or trembling voices, dependence on peers, frequent help-seeking, dislike of mathematics, and heart palpitations. Students in the moderate category exhibited anxiety such as dizziness, heart palpitations, and fear of failure. Meanwhile, students in the high category of mathematical problem-solving ability tended to experience anxiety only in the form of worry or fear of failure.